-10+8a=6(a-4)

Simple and best practice solution for -10+8a=6(a-4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -10+8a=6(a-4) equation:


Simplifying
-10 + 8a = 6(a + -4)

Reorder the terms:
-10 + 8a = 6(-4 + a)
-10 + 8a = (-4 * 6 + a * 6)
-10 + 8a = (-24 + 6a)

Solving
-10 + 8a = -24 + 6a

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-6a' to each side of the equation.
-10 + 8a + -6a = -24 + 6a + -6a

Combine like terms: 8a + -6a = 2a
-10 + 2a = -24 + 6a + -6a

Combine like terms: 6a + -6a = 0
-10 + 2a = -24 + 0
-10 + 2a = -24

Add '10' to each side of the equation.
-10 + 10 + 2a = -24 + 10

Combine like terms: -10 + 10 = 0
0 + 2a = -24 + 10
2a = -24 + 10

Combine like terms: -24 + 10 = -14
2a = -14

Divide each side by '2'.
a = -7

Simplifying
a = -7

See similar equations:

| [2+-3]=-4 | | 54=2x^2+12x | | 5-4x=2-3x | | -8(24)+15=x | | f+11=-9 | | 13=x*1.25 | | 2x+4x-3+10=10x-19 | | X+(-y)=-y+x | | 80=2l+2*14 | | 7=32(5x+8) | | -10.5p=-5-11p | | u=8a-56 | | 7 = 32(5x+8) | | 7e^4x+8=14 | | 6-2n=16 | | 9c-3d=c | | 4b-9b+3=-32 | | ln(x^2)+ln(9)=3 | | 16+5c=-29 | | 7x+6+9x+8=126 | | (9+9)x^2+(-4+8)x-30= | | [-4-3]=1 | | -15=a-40 | | 5x-1=14x-49 | | 2x+3y+5z=1 | | -5+7b+3=33 | | N+13=-4(-5n-8) | | y=4/3-2/3 | | 6x=12.96 | | 2x-3+3x-32=90 | | -8x^2+28xy+60y^2=0 | | 2b-10=3b+21 |

Equations solver categories